Isolation and Characterization of Pectic Polysaccharide Fraction from In Vitro Suspension Culture of Fumaria officinalis L. (10th October 2018) - Ognyanov, Manol; Georgiev, Yordan; Petkova, Nadezhda; Ivanov, Ivan; Vasileva, Ivelina; Kratchanova, Maria
Abstract : In the current study, an acidic polysaccharide from the in vitro suspension culture of Fumaria officinalis L. was obtained by extraction with 0.8% (w/v) aqueous ammonium oxalate. The polysaccharide fraction mainly consisted of galacturonic acid (41.0%), followed by galactose (7.3%) and arabinose (5.6%). This suggests the presence of arabinogalactan side chains in the rhamnogalacturonan-I segment of the studied pectin, which was mainly built up by homogalacturonan segments. The pectin was evaluated as low-methyl-esterified (45.0%) with degree of acetylation 3.4%. The polymer fraction was consisted of different molecular weight populations in the range of 6–600 kDa. The high amount of 4-L-hydroxyproline (11.7% of total protein) and the specific positive reaction to Yariv's phenylglycoside reagent indicated the presence of an arabinogalactan protein in the cell walls. The functional properties of the polysaccharide fraction were evaluated, as it possessed better water-holding capacity than oil-holding capacity. The studied pectin demonstrated significant foaming ability and promising emulsifying properties in a concentration 1%. Therefore, the isolated polysaccharide fraction could be successfully used as emulsifier and foaming agent in food products and pharmaceutical supplements.